Corrosion of Reinforcement in Relation to Presence of Defects at the Interface Between Steel and Concrete - Söylev, Tayfun Altuğ; Francois, R. (ASCE-AMER SOC CIVIL ENGINEERS, 1801 ALEXANDER BELL DR, RESTON, VA 20191-4400 USA, 2005)
In this study, steel-concrete interface defects were analyzed in order to define their potential to induce corrosion. Various types of steel-concrete interface defects were classified into two main groups: macrodefects and microdefects. Gaps formed beneath horizontal reinforcement as a result of bleeding and settlement of fresh concrete were analyzed for macrodefects. Microdefects presented no signs that could be identified by visual inspection and resulted not only from controlled pull-out of the steel bar but also from bleeding and settlement (but without the production of macrodefects as found with gap formation), Apart from interface defects, cover concrete porosity was defined as an intrinsic defect. The effect of these defects on reinforcement corrosion was investigated. Macrodefects have a direct effect on corrosion, whereas microdefects have no significant effect on Corrosion. Where the level of intrinsic defects was high, these had a greater effect on corrosion than interface macrodefects. The behaviors of conventional and self-compacting concrete (SCC) were compared. SCC was found to have better interface quality.
Keywords: Interfaces; Reinforcement; Concrete; Steel; Compaction; Corrosion; Silica Fume; Bars; Bond; Performance; Mortar; Arayüzler; Takviye; Beton; Çelik; Sıkıştırma; Korozyon; Silis Dumanı; Barlar; Bağ; Performans; Harç